Effective substances and mechanism of red ginseng on rats with spleen-deficiency syndrome based on the substance and energy metabolism as well as the "brain-gut" axis. (15th July 2023) - Zhang, Xu; Wang, Xiaotong; Shi, Rui; Ran, Xiaoku; He, Xiahong; Dou, Deqiang
Abstract: Ethnopharmacological relevance: Red ginseng (RG), a processed product of ginseng (GS), is a generally used qi -tonifying medicine in Traditional Chinese Medicine (TCM). According to the TCM principle, RG is also generally applied to spleen-deficiency syndrome (SDS) clinically for its warmer property. However, the effective substances and mechanism of RG on SDS have not been well investigated. Aim of the study: The aim of this study was to explore the effective substances and their mechanism of RG on SDS. Materials and methods: The SDS model was established with a compound factor method involving an irregular diet, excessive fatigue and sennae folium with a bitter-cold property. The medicine of RG was split by multi-mode separation methods and analyzed by ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS). The appearance indexes such as body weight, body temperature, swimming endurance, urine output, and water content of fecal were determined. The biochemical indexes such as D-xylose, SP, VIP and AChE in the digestive system, CRH, ACTH, CORT, E, T3, T4, T, E2 and 5-HT in the endocrine system, CS, NCR, IDH1, COX and Na + -K + -ATPase in the metabolism of substance and energy, cAMP and cGMP in the cyclic nucleotide system were analyzed by Enzyme-linked immunosorbent assay (ELISA) kits and biochemical kits. The serum metabolites were analyzed by UPLC-QTOF/MS. Furthermore, the gut microbiota and short-chain fatty acids (SCFAs) in feces were analyzed by 16S rRNA sequencing and headspace gas chromatography-mass method. Results: The pharmacological experiments showed that total saponin fraction (RGTSF), less polar fraction (RGLPF), and polysaccharides faction (RGPSF) significantly modulated the "brain-gut" axis-related indexes (the levels of VIP, AChE, and 5-HT). Besides, RGTSF also significantly modulated the hypothalamic-pituitary-adrenal (HPA) axis-related indexes as well as the substance and energy metabolism-related indexes (the levels of ACTH, CORT, A, Na + -K + -ATPase, COX, NCR and CS). RGPSF also significantly modulated the hypothalamus-pituitary-thyroid (HPT) axis-related indexes (the levels of T3 and T4). Secondly, metabolomics indicated that RGTSF could significantly regulate the abnormal metabolic pathways associated with the development of SDS, which involved steroid hormone biosynthesis, taurine and hypotaurine metabolism, primary bile acid biosynthesis, and amino acid metabolism. Subsequently, the study of gut microbiota indicated that RGLPF could increase the diversities of the gut microbiota and the relative abundance of Firmicutes in rats with SDS, while RGWEF significantly increased the relative abundance of Bacteroidetes . At the genus level, RGLPF could increase the relative abundance of Lactobacillus in rats with SDS and decrease that of Akkermansia . Meanwhile, the water-eluted fraction (RGWEF) showed a stronger regulation in SCFAs. Conclusion: It is for the first time that the effective substances of red ginseng on spleen-deficiency syndrome were studied systematically, and the different mechanisms of the RG fractions involved in substance and energy metabolism as well as the "brain-gut" axis were revealed. The present study demonstrated that RGTSF, RGPSF, and RGLPF were the effective substances of red ginseng for ameliorating spleen-deficiency syndrome, indicating that ginsenosides composed of primary and secondary saponins as well as polysaccharides were the main effective substances for red ginseng in ameliorating spleen-deficiency syndrome. Graphical abstract: Image 1 Highlights: It is the first time to elucidate the mechanisms of red ginseng and its fractions in treating spleen-deficiency syndrome. Red ginseng plays a role in tonifying spleen by regulating substance and energy metabolism as well as the "brain-gut" axis. The total saponin fraction, less polar fraction, and polysaccharides faction can treat spleen-deficiency syndrome well.